Foundations of marketing - Pride, William M.; Ferrell, O. C. (Cencage Learning, 2015)
Popular with readers from all backgrounds and interest levels, this book introduces them to the essentials and trends in marketing with visuals and stimulating, timely discussions. It includes coverage of marketing strategies and concepts such as social media, entrepreneurship, sustainability, globalization, and customer relationship management